IDENTIFIKASI KERAGAMAN SIFAT KUANTITATIF KAMBING MARICA DI KABUPATEN JENEPONTO (Identifcation of Quantitative Characteristic Diversity of Marica Goat in Jeneponto District) - F. Ashari; S.R. A. Bugiwati; L. Rahim; M.I. A. Dagong (Jurnal Ilmu dan Teknologi Peternakan, 2017)
The research objective was to identify the population, spread characteristics, and quantitative characteristics  of Marica  goat  in  Jeneponto  district  in  order  to  get more  information  about  the morphological differences between the Marica goat and Kacang goat.   The beneft of this research was  to  attain  an  accurate  scientifc  data  on  the  population  of  spread  character  and  quantitative characteristic  of  Marica  goat.  The  outcome  of  the  research  can  be  utilized  as  references  for government, researchers, and goat breeders  in  the preservation of Marica goat. This research was done by sampling the Marica goats at and Kacang goat as a comparison. The body dimensions were measured on body length, withers height, chest depth, hip height, chest girth, chest width, hip width, leg length, and body weight. The result showed that the Marica goat was only found around high altitude areas. The male Marica goat at 3-4 years of age was not found anymore. The total population of Marica goats recorded was 20 heads, and all of Marica goats have similarity in body dimensions with Kacang goats  as  an  effect of uncontrolled breeding between Marica goat  and Kacang goat. This experiment showed that there were no pure breed of Marica goat at Jeneponto district which is existing now. The homogeneity percentage of existing Marica goat was high (CV<20%), therefore it is not recommended to do the selection in that population